KEBIJAKAN IMPOR DAN PERSAINGAN USAHA KOMODITAS GARAM MASA AWAL PRESIDEN JOKOWI-JK TAHUN 2015-2016 - Asrul Raman (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2020)
This study aims to describe the political dynamics in the formulation of salt import policies in Indonesia during the early administrationin Jokowi-JK 2015-2016 which were characterized by the practice of unfair business competition in the form of rent-seeking and monopoly. The primary questions that will guide the researcher are (1) what is the portrait of salt import policy during the early Jokowi-JK administration? and (2) how the relationship between private actors and bureaucratic ones in the domain of salt import policy through the Regulation of Indonesian Trade Ministry No. 125/2015? As qualitative research with a descriptive approach, this research utilizes in-depth interviews, observation, document tracking, and document analysis techniques in which a number of bureaucrats,entrepreneurs, and salt farmers were used as informants to mine the data. The results of this study show that Nawacita's priority agenda in the form of an economic policy package became the main foundation for the formulation of import policy (the Regulation of Indonesian Trade Ministry No. 125/2015) which requires the government to abolish recommendations for import permits from the Ministry of Industry, import quotas, time of imports, and absorption of people's salt. As a result, political turmoil arose among salt farmers who considered the government reluctant to protect the salt of the people but instead prioritized the interests of entrepreneurs. Through such a policy, the state facilitated PT. Garam carries out a monopoly on the import of consumption salt to bring about the practice of unfair business competition between salt importers. This kind of political dynamics increasingly emphasizes that the formulation of public policies that do not go through a "fair" mechanism often enables the emergence of unfair business practices, monopoly, and rent-seeking.